Block-Based Models and Theorem Proving in Model-Based Development - Bernardeschi, Cinzia; Domenici, Andrea; Fagiolini, Adriano; Palmieri, Maurizio (Electronic Communications of the EASST, 2021)
This paper presents a methodology to integrate computer-assisted theorem proving into a standard workflow for model-based development that uses a block-based language as a modeling and simulation tool. The theorem prover provides confidence in the results of the analysis as it guides the developers towards a correct formalization of the system under development.